The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1152/japplphysiol.01410.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prior very-heavy intensity exercise on indices of aerobic function and high-intensity exercise tolerance

Abstract: Ferguson C, Whipp BJ, Cathcart AJ, Rossiter HB, Turner AP, Ward SA. Effects of prior very-heavy intensity exercise on indices of aerobic function and high-intensity exercise tolerance. J Appl Physiol 103: [812][813][814][815][816][817][818][819][820][821][822] 2007. First published May 31, 2007; doi:10.1152/japplphysiol.01410.2006.-A recent bout of high-intensity exercise can alter the balance of aerobic and anaerobic energy provision during subsequent exercise above the lactate threshold ( L). However, it re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
78
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 54 publications
10
78
0
5
Order By: Relevance
“…The 1/time model has commonly been utilized for parameter determination (Brickley et al, 2002, Ferguson et al, 2007, Ferguson et al, 2010, Pringle and Jones, 2002 …”
Section: Traditional Determination Of the Speed-time Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1/time model has commonly been utilized for parameter determination (Brickley et al, 2002, Ferguson et al, 2007, Ferguson et al, 2010, Pringle and Jones, 2002 …”
Section: Traditional Determination Of the Speed-time Relationshipmentioning
confidence: 99%
“…CP is associated with the muscle's aerobic power (Gaesser and Wilson, 1988, Gaesser et al, 1995, Jenkins and Quigley, 1992, McLellan and Cheung, 1992, Miura et al, 1999, Miura et al, 2000, Moritani et al, 1981, Moritani et al, 1981, Poole et al, 1990, while W` represents predominantly 'anaerobic' characteristics (Ferguson et al, 2007, Ferguson et al, 2010, Gaesser and Wilson, 1988, Jenkins and Quigley, 1992, Miura et al, 1999, Miura et al, 2000, Moritani et al, 1981, Poole et al, 1990 and is determined, in part, by intramuscular energy stores of phosphate, glycogen, and oxygen (Miura et al, 1999, Miura et al, 2000, Monod and Scherrer, 1965 as well as by accumulation of fatigue-inducing metabolites (Coats et al, 2003, Ferguson et al, 2007. CP demarcates the heavy-severe domain boundary in that, at or below CP a general steady state is achieved , Poole et al, 1988 , Poole et al, 1988.…”
Section: Introductionmentioning
confidence: 99%
“…It is also evident that W= is a constant term that determines the limit of exercise tolerance (T lim ) for severe-intensity exercise (21, 55). Intramuscular energy stores (35,36,38), the accumulation of fatigue-inducing metabolites (7,18,21,28), and/or the magnitude of the severe-intensity domain (5, 51) have all been postulated to determine W=. Building evidence supports that complete utilization of W= is associated with consistent muscle phosphocreatine ([PCr]), inorganic phosphate ([P i ]), and hydrogen ion concentration ([H ϩ ]) perturbations, which may limit the amount of work performed above CP (28,43,51).…”
mentioning
confidence: 99%
“…Furthermore, there are no many clear evidences about the recovery period between warm-up and the performance. From the results from this study and many others already existing evidences it can be said that the recovery period between high intense swimming during warmup and performance should be long enough or there is going to be visible drop in the results (Bishop, 2003;Ferguson et al, 2007;Palmer et al, 2009). In the case of this study, very short recovery period after high intense swimming caused drop in the performance, compared to the 100 meters swim performed after sessions with low intensity swimming.…”
Section: Resultsmentioning
confidence: 57%
“…Some previous studies showed that very short recovery time between warm-up session and the performance can cause dropping in the performance if the warm-up session was at higher level of intensity (Burnley et al, 2005;Ferguson et al, 2007). As many authors suggest, for removing lactic acid from the blood it is necessary to pass some time or to spend that time in easy swimming or massage (Bishop, 2003;Hoffman, 2002;Maglischo, 2003).…”
Section: Discussionmentioning
confidence: 99%